MEDICINA POPULAR E COMUNIDADES RURAIS DA REGIÃO DA SERRA DAS ALMAS, PARANÁ: O AMÁLGAMA COSMO-MÍTICO-RELIGIOSO TRADICIONAL - Clarindo, Maximillian Ferreira (2014)
This research has as its main objective understanding the reproduction of folk medicine in Serra das Almas, located in the District of Três Córregos in Campo Largo, Paraná State, taking into account the material and symbolic dimensions that constitute this system of traditional knowledge and practices. To this end, we discuss the folk medicine and the health-disease process in a contextualized manner to the rural way of life of families living in the region. In this direction, the material and symbolic elements that integrate traditional knowledge were also characterized, as well as the ways in which the subjects territorialize their practices and knowledge were identified. The investigation is divided into four sections. In the first, of theoretical reflection, we debate about the relationship of communities to their respective territories, as well as with the region formed by the connection of local territoriality over various networks, among them, the network reciprocity woven through folk medicine. Within this regional analysis, it is noted that the articulation of the global with the local did not overwrite the notion of small regions, nor dismantled the traditional way of life (identities). On this understanding, we also seek in the first chapter to understand the extent to which modernizing processes (postmodernity) focus on identity (individual and collective), the rustic Catholicism (adaptation of Catholicism to the rural areas) and in popular knowledge in family health of the region. It was observed that communities do not go exclusively towards to the incorporation of new elements and habits into their daily lives, but rather articulate a logic idea of association between the ancient and the modern (change and permanence). We also speak of antagonism between modern medicine and the medicine of the people. It is thought that the gathering of such knowledge, one guided by rationality and another organized by the cognitive matrix, may generate good results for science and encourage the preservation of traditional knowledge. In terms of methodology, it is about a qualitative research guided the analysis of the narratives, phenomena, actions and daily practices of individuals. Thus, we began with participant observation and then we started open interviews, analysis of documents, photographs and other forms of observation. Then, we concluded that folk medicine is an amalgam of knowledge, work conducted by faith healers and the people who dominate the management of local agro-biodiversity in the preparation of home remedies. It is a hybrid of a traditional knowledge that gives a holistic view of the health-disease process in the region, whose reproduction has had obstacles over the years, among other factors, by the tension in the disputed territory between the different actors, migration to the faithful evangelical churches, lack of space for dialogue in modern medicine and by the action of modernizing processes (incorporating electronic media, etc.)